The relationship between the consumption of digital media, participation and political efficacy. A study about young university students in Colombia (2018)
Introduction: The political participation is essential for the democratic consolidation, considering that through social engagement, citizens are able to achieve consensus and develop public deliberations. This is especially important in Colombia, a society surrounded by an armed conflict for more than five decades, as well as devastated by drug trafficking mafias, economic breach and the lack of presence of the State in some regions, among some of them. Methodology: Using a survey to 581 Colombian young university students, we evaluated the relationship between four categories that can be determinant for democratic quality, such as the consumption of digital media, online and offline participation and political efficacy. Results and conclusions: In our findings, besides a link between aforementioned variables, we observe a low consumption of traditional media in respondents, as well as a lack of participation -online and offline-. © 2018, University of La Laguna. All rights reserved.